2023
DOI: 10.1186/s13048-022-01088-9
|View full text |Cite
|
Sign up to set email alerts
|

A signature based on glycosyltransferase genes provides a promising tool for the prediction of prognosis and immunotherapy responsiveness in ovarian cancer

Abstract: Background Ovarian cancer (OC) is the most fatal gynaecological malignancy and has a poor prognosis. Glycosylation, the biosynthetic process that depends on specific glycosyltransferases (GTs), has recently attracted increasing importance due to the vital role it plays in cancer. In this study, we aimed to determine whether OC patients could be stratified by glycosyltransferase gene profiles to better predict the prognosis and efficiency of immune checkpoint blockade therapies (ICBs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…B4GALT5 is involved in the formation of complex-type N-glycans, which are important for protein folding, stability, and function [27] . Dysregulation of B4GALT5 expression or activity can lead to altered glycosylation patterns, which have been implicated in a variety of diseases, including cancer, cardiovascular disease, and neurodegenerative disorders [28][29][30][31] . For instance, several studies have demonstrated the potential of B4GALT5 downregulation to ameliorate insulin resistance by promoting adipogenic commitment and reducing M1 macrophage in ltration [32] .…”
Section: Discussionmentioning
confidence: 99%
“…B4GALT5 is involved in the formation of complex-type N-glycans, which are important for protein folding, stability, and function [27] . Dysregulation of B4GALT5 expression or activity can lead to altered glycosylation patterns, which have been implicated in a variety of diseases, including cancer, cardiovascular disease, and neurodegenerative disorders [28][29][30][31] . For instance, several studies have demonstrated the potential of B4GALT5 downregulation to ameliorate insulin resistance by promoting adipogenic commitment and reducing M1 macrophage in ltration [32] .…”
Section: Discussionmentioning
confidence: 99%
“…miR-491-5p promotes the progression of acute myeloid leukemia by regulating the expression of B4GALT5 and the PI3K/AKT signaling pathway. The increased mRNA and protein levels of B4GALT5 are associated with poor prognosis for hepatocellular carcinoma, ovarian cancer, cervical cancer and other cancers [ 32 , 33 , 34 , 35 ]. In patients with pancreatic cancer, we discovered that increased B4GALT5 expression was substantially correlated with shorter overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation is highly associated with aberrant glycosylation [ 25 ]. Previous studies have found that glycosylation-related genes are associated with the prognosis of patients with breast [ 26 ], ovarian [ 27 ], liver [ 28 ] and cervical cancer [ 29 ]. However, current studies on glycation in PC mainly focus on the influence of individual glycation type or single glycation enzyme on tumor progression [ 30 , 31 ], and there are no relevant reports on the expression status of numerous glycation related genes in PC and their relationship with PC microenvironment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%